RECYCLING SHADOWS: TOLKIEN’S INFLUENCE ON ROWLING’S COMPOSITION OF VOLDEMORT AND THE DEMENTORS - Rossi, Cido (Abusões, 2024)
The shadow archetype is one of the most productive in fiction, where it usually manifests through personifications, characters which embody its principles of haunting, permanent returning, questioning, and debt: the villains and the creatures of the dark. The embodiment of the shadow is a compositional procedure that, in the case of Fantasy worlds, works by the means of creatively recycling and refiguring elements of previous personifications of the shadow. Thus, departing from a short theoretical consideration on Fantasy as the branch of the Fantastic that is the best place for dealing with the shadow archetype, we intend to demonstrate, as an example on how the two procedures of personification of the shadow work in fiction, the influence of Tolkien on J. K. Rowling’s composition of the villain Voldemort and the Dementors in her Harry Potter series.